Sobre a poética da orquestração acústica de Glenn Gould: análise e aplicação prática - Moreira, Fabricio do Rosário (2023)
This work aims to correlate aspects of pianist Glenn Gould's musical experience through some categories of the Audiotactile Music Theory such as: neo-auratic coding, the audiotactile principle and the visual matrix. Each of these categories will support, respectively, the study of the following topics in Gould's artistic work: the editing of his recordings, the creation of acoustic orchestration, corporeality and the alteration of scores. In addition to theoretical investigation, this research also has a practical perspective, which includes the application of acoustic orchestration to the piece “Jeux d’eau” by Maurice Ravel, recorded by the author of this study.